Albumin-to-creatinine ratio as a predictor of all-cause mortality and hospitalization of congestive heart failure in Chinese elder hypertensive patients with high cardiovascular risks - Mingming Liu; Yan Liang; Jun Zhu; Yanmin Yang; Wenfang Ma; Guozheng Zhang (BMC, 2018)
Abstract Background Data are limited with regard to the relationship of albuminuria and major adverse cardiovascular events (MACE) in Chinese elder patients with high cardiovascular risk. Methods We did a retrospective cohort study using Chinese elder patients with high cardiovascular risks (n = 1474) to identify the association of albumin-to-creatinine ratio (ACR) and the incidence of MACE and all-cause mortality. Individuals were followed up from January, 2002 to November, 2007. The all-cause mortality and MACE, composite outcome of cardiovascular death, myocardial infarction, stroke and hospitalization of congestive heart failure were defined as primary endpoint. Results During the median following up of 56 months, 213 patients developed primary endpoint and 117 patients died. Patients with higher baseline urinary ACR (> 30 mg/g) experienced a nearly 2-fold of all-cause mortality and a 3-fold of heart failure hospitalization than those with lower baseline urinary ACR (≤10 mg/g).MACE, cardiovascular death, stoke and myocardial infarction showed no difference in three grades of urinary ACR (> 30 mg/g, 10 mg/g-30 mg/g, ≤10 mg/g) in this cohort. Patients above 65 years with increased ACR tended to experience higher mortality risks, and the association of increased ACR with higher hospitalization of congestive heart failure seemed to be more prominent in patients below 65 years than above 65 years. Conclusions In this post hoc analysis of Chinese individuals with high cardiovascular risks, higher urinary ACR was associated with higher all-cause mortality and heart failure hospitalization. Further studies are needed to find out whether there is age-specific ACR cutoff point.